Blood Loss Estimation in Small Animals and Assessment of a Pictorial Tool to Improve Accuracy in a Global Population of Veterinary Anesthesia Staff - Cumming, Scott H.; Martinez-Taboada, Fernando (Frontiers in Veterinary Science, 2020)
Visual estimation of blood loss is the most common form of evaluating intraoperative haemorrhage, and is also the most inaccurate. This study investigated the visual estimation accuracy of a global population of anaesthesia staff and students as an initial estimation and also with the assistance of a pictorial guide. A voluntary, two-part, online, anonymous survey was distributed to members of two email databases with an interest in anaesthesia, including students, nurses, interns, residents, general practitioners, and specialists. The survey consisted of visual and brief descriptive depictions of blood loss scenarios involving small animals, principally including images of common surgical items and receptacles containing a blood-like substance. Each participant estimated the blood volume (in mL) for each scenario twice, initially (Pre-Guide [PGD]) and then with the aid of a pictorial guide (With-Guide [WGD]). The pictorial guide used similar images labelled with corresponding volumes. Data was analysed for normality with the Shapiro-Wilks test, corrected to absolute error and compared for statistical significance using the Wilcoxon signed-ranks test or the Kruskal-Wallis test as appropriate. The overall raw PGD phase median estimation error was - 27 mL (range -99 to 248 mL). The PGD raw median error increased with scenario complexity. There were no differences between role, gender, experience, or country of origin. The overall median raw estimation error for the WGD phase was 13 mL (range -80 ml to 143 mL) (p = 0.0128). Visual blood loss estimation is inaccurate amongst veterinary anaesthetists and associated staff, showing decreasing accuracy with increasing complexity. A pictorial guide improves the accuracy generally, and specifically for more complex scenarios which are likely to reflect the clinical situation.